2017
DOI: 10.1016/j.jsha.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac manifestations of atrial myxomas

Abstract: Primary cardiac tumors are extremely rare and constitute only about 5% of all cardiac tumors. Cardiac myxomas are noncancerous primary tumors of the heart and constitute about of 50% of all primary heart tumors. Left-sided atrial myxomas are more common than right-sided atrial myxomas. Atrial myxomas can lead to a triad of complications. The most common symptoms are associated with obstruction due to the size and location of the tumor. The next most common symptoms are associated with pulmonary and systemic em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 47 publications
1
66
0
6
Order By: Relevance
“…Anatomically, atrial myxomas are mostly pedunculated and soft, and which are in consistency with a smooth, villous, or irregular surface. Atrial myxomas predominantly occur between the third and the sixth decades of life and show a 2.05:1 female predominance (3). Over 75% of myxomas originate from the left atrium, 18% of them from the right atrium, while less than 5% are found in bilateral atrium (4).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomically, atrial myxomas are mostly pedunculated and soft, and which are in consistency with a smooth, villous, or irregular surface. Atrial myxomas predominantly occur between the third and the sixth decades of life and show a 2.05:1 female predominance (3). Over 75% of myxomas originate from the left atrium, 18% of them from the right atrium, while less than 5% are found in bilateral atrium (4).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac myxomas are usually pedunculated and have a smooth, villous or friable surface. Smooth myxomas are known for obstructive complications, whereas villous and friable ones tend to cause embolic complications [22]. The myxoma in the case we are presenting was friable according to the pathology report.…”
Section: Discussionmentioning
confidence: 84%
“…The incidence rate of atrial myxoma was reported 0.0017% to 0.19% [1]. Cardiac myxoma may cause the three major symptoms: obstructive symptoms, constitutional symptoms, and embolic symptoms [5]. The obstructive symptoms were resulted from obstruction of cardiac outflow, leading to left heart failure, pulmonary congestion, mitral valve regurgitation or stenosis.…”
Section: Discussionmentioning
confidence: 99%